(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper presents an adaptive cross approximation (ACA) accelerated Isogeometric Boundary Element Method (IBEM) using Non-Uniform Rational B-Splines (NURBS) as shape and interpolation functions. Provided that NURBS are used in CAD programs to describe geometry, the mesh generation in the IBEM is no longer necessary. For large and complex models the traditional BEM quickly becomes very time and memory consuming and, to overcome this problem, the use of ACA is considered in this paper. Mesh generation is also found to be one of the most time consuming tasks in numerical simulations, therefore the coupling between ACA and IBEM is very promising. Numerical examples are presented in order to assess the accuracy and feasibility of the method.